(untitled) (Research, Society and Development, 2021)
Introduction: The role of the obstetric nurse in the setting of childbirth care shows numerous advantages, in which less interventionist care entails less risk to maternal health. Objective: To identify the main strategies of the obstetric nurse for the reduction of the interventional methods during the normal delivery. Method: Bibliographic study, descriptive type of integrative literature review. The bases used for data collection were: BVSalud, SciELO, BDENF, MEDLINE / PubMed and Documents from the Ministry of Health (MS), with articles published from 2015 to 2020. There was no need for approval by the Research Ethics Committee. Results and discussion: Articles were selected for three categories: (A) Sprinkler bath; (B) Facilitating exercises; and (C) Comfortable position for delivery. It was proved that the hot bath is the strategy most used by nurses; the main facilitating exercises were breathing, the use of the Swiss ball and walking; encouraging the adoption of different positions during childbirth contributes to a better evolution of the birth process. Conclusion: There is a range of possibilities that the obstetrical nurse can use in assisting normal childbirth, however they need to be implemented in everyday life, since there is still a great deal of attachment to traditional methods of childbirth.